A QUALITATIVE STUDY OF VIBRIO PARAHAEMOLYTICUS (SAKAZAKI ET AL) IN ETROPLUS SURATENSIS (BLOCH) AND METAPENAEUS DOBSONI (MIERS) FROM COCHIN BACKWATER - PRADEEP, R; LAKSHMANAPERUMALSAMY, P (Fishery Technology, 2017)
Seasonal variation of Vibrio parahaemolyticus in fish (Etroplus sauratensis) and prawn (Metapenaeus dobsoni) was monitored from March 1982 to February 1983. Analyses of total viable count, vibrio-like organisms, V. parahaemolyticus like organisms and V. parahaemolyticus showed that they occur more in prawn than in fish. In a more polluted environment, the counts of V. parahaemolyticus associated with fish was found to be higher than in prawn.